Bi-reforming of methane on Ni/SBA-15 catalyst for syngas production: Influence of feed composition - Singh, Sharanjit; Mahadi, Bahari; Bawadi, Abdullah; Phuong, Pham T. T.; Truong, Quang Duc; Vo, Dai-Viet N.; Adesina, Adesoji A. (Elsevier, 2018)
Bi-reforming of methane (BRM) was evaluated for Ni catalyst dispersed on SBA-15 support prepared by hydrothermal technique. BRM reactions were conducted under atmospheric condition with varying reactant partial pressure in the range of 10–45 kPa and 1073 K in fixed-bed reactor. The ordered hexagonal mesoporous SBA-15 support possessing large specific surface area of 669.5 m2 g−1 was well preserved with NiO addition during incipient wetness impregnation. Additionally, NiO species with mean crystallite dimension of 14.5 nm were randomly distributed over SBA-15 support surface and inside its mesoporous channels. Thus, these particles were reduced at various temperatures depending on different degrees of metal-support interaction. At stoichiometric condition and 1073 K, CH4 and CO2 conversions were about 61.6% and 58.9%, respectively whilst H2/CO ratio of 2.14 slightly superior to theoretical value for BRM would suggest the predominance of methane steam reforming. H2 and CO yields were significantly enhanced with increasing CO2/(CH4 + H2O) ratio due to growing CO2 gasification rate of partially dehydrogenated species from CH4 decomposition. Additionally, a considerable decline of H2 to CO ratio from 2.14 to 1.83 was detected with reducing H2O/(CH4 + CO2) ratio due to dominant reverse water-gas shift side reaction at H2O-deficient feedstock. Interestingly, 10%Ni/SBA-15 catalyst was resistant to graphitic carbon formation in the co-occurrence of H2O and CO2 oxidizing agents and the mesoporous catalyst structure was still maintained after BRM. A strong correlation between formation of carbonaceous species and catalytic activity was observed.